The awakening of Asia - Hyndman, H. M. (Henry Mayers), 1842-1921. (Melbourne : Cassell, 1919)
A study of the influence of the white man on the Far East.
Index: p.285-291.
Keywords: Asia -- History; East Asia -- History; Asia -- Foreign relations -- Europe; East Asia -- Foreign relations -- Europe